Hubungan Kualitas Pelayanan Administrasi Dengan Kepuasan Pasien Di Wilayah Kerja Puskesmas Piru Kabupaten Seram Bagian Barat Tahun 2023 - Abd. Rijali Lapodi; Herlin Sinay; Zulfikar Lating; Ilyas Ibrahim; Muhamad Adi Sasono (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Patient satisfaction is still an important issue in relation to administrative services as an indicator of improving the quality of service to patients. Therefore, the quality of administrative services needs to be paid attention to in order to have a positive impact on patient perceptions and experiences. This study aims to determine the level of satisfaction with several indicators of the relationship between the quality of administrative services, namely physical evidence (tangible), reliability, responsiveness, assurance, sympathy (empathy) with patient satisfaction in the Piru Health Center Working Area, Seram Regency. West Region. The type of research used was analytical observational with a cross sectional design with a sample size of 44 people. Data collection was carried out through primary data, namely data taken from the results of patient questionnaire answers and secondary data, namely data taken from initial research data collection. Data were analyzed univariately and bivariately using the chi square statistical test. The univariate test results of this research show that several indicators of the quality of administrative services are classified as quite good. Meanwhile, the results of the bivariate test of the relationship between the quality of administrative services and patient satisfaction prove a significant result, namely with a value (p < a = 0.05). each indicator of the quality of administrative services with patient satisfaction, each indicator of physical evidence (tangible) with a p value = 0.000, reliability indicators with a p value = 0.000, responsiveness indicators with a p value result = 0.000, assurance with a p value = 0.000, empathy with a p value = 0.000. The conclusion of this research is that there is a very significant relationship between the quality of administrative services and patient satisfaction in the Piru Health Center Working Area, West Seram Regency. It is hoped that the Telaga Village Pustu will pay more attention to administrative services to patients so that the services provided can meet the level of patient satisfaction better in the future.